FREE POWER-SEMICOMMUTATIVE TERNARY GROUPOIDS - Celakoska-Jordanova, Vesna; Celakoska, Emilija; Miovska, Valentina (Matematichki Bilten, 2018)
A description of free objects in the class \(\mathcal{P}_{sc}\) of power-semicommutative ternary groupoids and a proper characterization of the class of free objects in \(\mathcal{P}_{sc}\) by means of \(\mathcal{P}_{sc}\)-injective ternary groupoids are obtained.